Carbodiimide crosslinked decellularized lenticules as a drug carrier for sustained antibacterial eye treatments. (1st March 2023) - Rao, Jing; Zhou, Qizhi; Chen, Jiansu; Gu, Jianing; Wang, Yini; Liu, Yonghuan
Abstract: In this study, the drug-loading and antibacterial activity of carbodiimide/N-hydroxysuccinimide (EDC/NHS) crosslinked decellularized lenticules (CDLs) were evaluated. Small incision lenticule extraction derived lenticules were decellularized and modified with crosslinking concentrations of 0.00 (E/L00, non-crosslinked), 0.01 (E/L01), 0.05 (E/L05) and 0.25 mmol (E/L25) EDC per mg lenticules at 5:1 EDC/NHS ratios with non-decellularized non-crosslinked lenticules (NDLs) as controls. NDLs and EDC/NHS CDLs had similar water contents. The light transmittance percentages (400–800 nm) were 91.55 ± 1.16%, 88.68 ± 1.19%, 80.86 ± 1.94%, 85.12 ± 2.42% and 85.62 ± 2.84% for NDLs, E/L00, E/L01, E/L05 and E/L25, respectively ( P < 0.01). The EDC/NHS CDLs (diameter: 6.36 ± 0.18 mm; central thickness: 117.31 ± 3.46 μm) were soaked in 3% (wt./vol.) levofloxacin (LEV) solution for 3 h. The drug release concentrations of LEV-impregnated EDC/NHS CDLs were determined by high-performance liquid chromatography. Zone inhibition (ZOI) against Staphylococcus aureus of E/L01, E/L05 and E/L25 were superior to E/L00 CDLs ( P < 0.01) and among the different crosslinked groups, E/L05 lenticules produced the largest ZOIs and their drug concentration release over 21 d was the highest. EDC/NHS crosslinking can improve the drug-loading effect and antibacterial activity of decellularized lenticules. LEV-impregnated EDC/NHS CDLs are promising drug delivery carriers.